P089 Loneliness and sleep duration among healthy older adults in Southeast Queensland, Australia. (7th October 2021) - Lam, J; Mann, D; Pattinson, C; Allan, A; Smith, S; Baxter, J
Abstract: Introduction: The relationship between sleep duration and loneliness among healthy older adults is not fully understood. Shorter sleep duration and increased variability of sleep timing (sleep onset and wake time) have recently been shown to have adverse health outcomes in younger adults. While physiological stressors associated with loneliness are likely distinct, we hypothesise that older adults who identify as lonely have reduced sleep duration and increased variability of sleep timing. Methods: Older individuals (N=60) without significant co-morbidities were recruited via convenience sampling. Participants completed the de Jong Giervield Loneliness Scale and wore an actigraph for up to 2 weeks. Sleep metrics from actigraphy (sleep onset and wake times, and SD) were determined by algorithm assisted human scoring. Results: Valid data was retrieved from N=37 participants (age 83±6.8 years [mean±SD]). There were no significant differences in demographics between those in the lonely (N=19) and not lonely (N=18) groupings. There was substantial heterogeneity in individual participant's sleep metrics, both within and between groupings. The average sleep onset time was similar between groups, however lonely participants typically woke earlier resulting in slightly shorter sleep duration. Variability in sleep onset and wake times was reduced in lonely participants. Discussion: While shorter sleep duration was expected, we did not anticipate the reduction in sleep timing variability amongst those defined as lonely; more regular sleep periods have previously been associated with better outcomes. We did not see statistically significant differences between our groups, possibly due to sample size limitations, however, the unexpected trend warrants further investigation.